TRANSIENT BEHAVIOUR IN GLUCOSE/OXYGEN BIOFUEL CELLS - Yan, Han (My University, 2009)
In this thesis, solutions to the problem of low power density caused by pH
deviation in anode and cathode of a glucose/oxygen based enzymatic fuel cell using GOx and FMCA are provided. Moreover, conclusive evidence of a large active area in this type of fuel cell is determined using a transient state study. The complete process of electrical double layers formation is described.
A survey of the solutions to low power density caused by pH deviation is conducted and two feasible alternatives are suggested. The first alternative, using Tris buffer with no alkaline ions resulted in even larger pH gradient. The second alternative: using anion exchange membrane (AEM) successfully reduced the pH gradient by introducing lower power density than the biofuel cells using a Nafion membrane. It was proven that the high internal resistance of the AEM is responsible for the drop in energy output ofthe biofuel cell.
A transient study was conducted on the biofuel cells in order to investigate the
internal resistance of the components. A discrepancy was found when applying the
rarely-mentioned internal circuit model to biofuel cells. The model predicted a much
larger surface area for the electrode than was physically measured for the cells. It is
therefore concluded that the proposed electrochemical double layers are in the electrolyte as well as on the interface. Finally, a detailed description of electron/proton double layer in the electrolyte associated with each reaction step is given, assuming that double layers can be found on the enzymes and mediators.
A complete list of requirements for equivalent circuit is portrayed for our glucose/oxygen enzymatic biofuel cell. The equivalent circuit suggests a possible
direction for future biofuel cell research.
Keywords: Materials Science and Engineering; Materials Science and Engineering